Reviews of recent publications (Studies in 20th & 21st Century Literature, 2009)
Bigsby, Christopher. Remembering and Imagining the Holocaust: The Chain of Memory by Roxane Riegler Bruce, Iris. Kafka and Cultural Zionism. Dates in Palestine by Bettina Matthias Haase, Christine. When Heimat Meets Hollywood: German Filmmakers and America, 1985-2005 by Maria Stehle Herzog, Dagmar. Sex after Fascism: Memory and Morality in Twentieth-Century Germany by Sabine Hake Iossel, Mikhail and Jeff Parker. Amerika. Russian Writers View the United States by Yuliya Minkova Macksey, Richard and Eugenio Donato, eds. The Structuralist Controversy: The Languages of Criticism and the Sciences of Man by Safoi Babana-Hampton Magnarelli, Sharon. Home is Where the (He)art Is: The Family Romance in Late Twentieth-Century Mexican and Argentine Theater by Margo Milleret Matthias, Bettina. The Hotel as Setting in Early Twentieth-Century German and Austrian Literature: Checking in to Tell a Story by Susanne Kelley McGlothlin, Erin. Second-Generation Holocaust Literature: Legacies of Survival and Perpetration by Jennifer Cameron Taberner, Stuart, ed. Contemporary German Fiction: Writing in the Berlin Republic by Alexandra Merley Hill Walter Frisch. German Modernism: Music and the Arts by Jill Suzanne Smith
Keywords: Christopher Bigsby; Remembering and Imagining the Holocaust: The Chain of Memory; Roxane Riegler; Iris Bruce; Kafka and Cultural Zionism Dates in Palestine; Christine Haase; When Heimat Meets Hollywood: German Filmmakers and America 1985-2005; Maria Stehle; Dagmar Herzog; Sex after Fascism: Memory and Morality in Twentieth-Century Germany; Sabine Hake; Mikhail Iossel; Jeff Parker; Amerika Russian Writers View the United States; Yuliya Minkova; Richard Macksey; Eugenio Donato; The Structuralist Controversy: The Languages of Criticism and the Sciences of Man; Safoi Babana-Hampton; Sharon Magnarelli; Home is Where the (He)art Is: The Family Romance in Late Twentieth-Century Mexican and Argentine Theater; Margo Milleret; Bettina Matthias; The Hotel as Setting in Early Twentieth-Century German and Austrian Literature: Checking in to Tell a Story; Susanne Kelley; Erin McGlothlin; Second-Generation Holocaust Literature: Legacies of Survival and Perpetration; Jennifer Cameron; Stuart Taberner; Contemporary German Fiction: Writing in the Berlin Republic; Alexandra Merley Hill; Walter Frisch; German Modernism: Music and the Arts; Jill Suzanne Smith